2019
DOI: 10.32479/ijeep.8011
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gross Domestic Product and Population Growth on Co2 Emissions in Indonesia: An Application of the Ant Colony Optimisation Algorithm and Cobb-Douglas Model

Abstract: Gross domestic product (GDP) is one indicator for measuring a country's economic growth. However, the increase in GDP and population growth are affecting CO 2 emissions. This study analyses the effects of GDP and population density on CO 2 emissions in Indonesia. To this end, it used the Cobb-Douglas model, and parameter estimation using Ant Colony Optimisation algorithm. The analysis of the results reveals that GDP and population density influence CO 2 emissions in Indonesia significantly, and significantly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
1
4
0
7
Order By: Relevance
“…The coefficient of income per capita (LnGDP) is statistically significant at 1% level in the fixed effects model, indicating that market size and economic growth boosts climate change and environmental pollution. The empirical studies of Amador et al (2017), Antonakakis et al (2017), Balogh and Jámbor (2017), Bashir et al (2019), andSukono et al (2019) also supported our result.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The coefficient of income per capita (LnGDP) is statistically significant at 1% level in the fixed effects model, indicating that market size and economic growth boosts climate change and environmental pollution. The empirical studies of Amador et al (2017), Antonakakis et al (2017), Balogh and Jámbor (2017), Bashir et al (2019), andSukono et al (2019) also supported our result.…”
Section: Resultssupporting
confidence: 91%
“…The recent empirical research (Omri and Kahouli 2014;Saidi and Hammami 2015;Amador et al 2017;Antonakakis et al 2017;Balogh and Jámbor 2017;Bashir et al 2019;Bilan et al 2019;Sukono et al 2019) proved that it is causality between carbon dioxide emissions and economic growth. Sukono et al (2019) demonstrated that growth and population are directly correlated with CO 2 emissions in Indonesia. Bashir et al (2019) examined the causality between human capital, energy, carbon dioxide emissions, and growth utilizing a Vector Error Correction Model (VECM) and Granger causality method in Indonesia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…When the population density and EG of a country increases, people's purchasing power also increases. As a result, the demand for energy consumption increases, which eventually enhances the CO 2 E (Sukono et al, 2019). The Malthusian idea that the population puts pressure on the resources of a country that causes environmental degradation is of great importance (Andrews, 2020;Malthus, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan data yang diambil dari Badan Pusat Statistik, jumlah penduduk di Indonesia pada tahun 2019 adalah sebesar 266,911,900 jiwa, yang terdiri dari 134,025,600 laki-laki dan 132.886.300 perempuan. Indonesia menempati posisi keempat sebagai negara dengan populasi terbesar di seluruh dunia (Sukono et al, 2019). Berdasarkan The World Bank, laju pertumbuhan penduduk di Indonesia pada tahun 2019 adalah sebesar 1.1% dan Berdasarkan tabel di atas, jumlah penduduk terpadat di Indonesia berada di Jawa Barat, diikuti oleh Jawa Timur, dan Jawa Tengah.…”
Section: Sumber: International Monetary Fundunclassified